THE INFLUENCE OF TRAINING, ADDITIONAL INCOME, AND DISCIPLINE OF EMPLOYEE TOWARDS THE PERFORMANCE OF CIVIL SERVANTS IN THE REGIONAL APPARATUS ORGANIZATION OF PALU CITY - Sukryani, Dewi; Thahir, Harifuddin; Mahardiana, Lina (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This research aims to find out the influence of Work Training, Additional Income, and Discipline of Employee towards the Performance of Civil Servants in the Regional Apparatus Organization in Palu city. The research sample were 118 respondents of Echelon III Civil Servants in Palu City who was selected through a simple random sampling technique. Data were analyzed using multiple linear regression analysis. The results of the research show that work training, additional income, and work discipline simultaneously have a significant influence on performance of employee in the Regional Apparatus Organization of Palu city. Work training has a positive and significant influence on performance of employee in the Regional Apparatus Organization of Palu city. Additional income has a positive and significant influence on performance of employee in the Regional Apparatus Organization of Palu city. Work discipline has a positive and significant influence on performance of employee in the Regional Apparatus Organization of Palu city. Keywords: Training, Additional Income, Employee Discipline and Performance